Pemikiran Ulama’ NU Jawa Timur tentang Ontologi dan Epistimologi Islam Liberal - Muhammad Fahmi Hidayatullah (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2019)
Religious liberalism in Indonesia, which until now is still a hot topic, is framed in the (cultural) sciences. This research is just the opposite, looking for the nature of liberalism and certainly contrary to the basic ideology of the state. The type of research used is descriptive qualitative with a case study approach. The content of the study includes: the nature and characteristics of emerging and developing liberal Islamic ideas in Indonesia. The thinking of liberalism is very different from inclusiveness even though its essence has several similarities. This research outlines the nature of liberalism and the characteristics that lead to its thinking in several views of NU Ulama’ in East Java. Allegations against traditional Ulama' which are considered almost or equal to left-line Islamic thinkers need to be straightened through the results of this study. Keywords: Ontology, Epistimology, Liberal Islam, Traditional Ulama